The Influence of Teachers' Professional Competence and Social Competence on The Implementation of Bilingual Class at Private School, Jakarta - Laurentia Bawole, Ruth; Limbong, Mesta (International Journal of Educational Management and Innovation, 2025)
Background/Purpose: Improving the quality of education indeed cannot be separated from the critical role of a teacher. A teacher must have and hone competencies to realize national education goals. This study aims to determine the influence of teachers' professional and social competence on implementing bilingual classes in ND schools. Materials/Methods: The method used in this study is a quantitative approach with a survey method. The respondents in this study are teachers in the elementary and junior high units of ND schools. The number of respondents in this study was 32 teachers. This study uses a questionnaire instrument with the Likert model and multiple linear regression analysis. This study explores the influence of teachers’ professional and social competence on implementing bilingual classes at ND Puri Indah School, Jakarta. This research used a quantitative approach with regression analysis to examine the influence of teachers’ professional and social competence on implementing bilingual classes. Results: The professional competence has a minimal adverse effect on bilingual class implementation (regression coefficient = -0.011), while social competence contributes positively (regression coefficient = 0.176), accounting for 37.6% of the variance. Combined, both competences explain 74% of the effectiveness in implementing bilingual education. Conclusion: The results underscore the greater role of social competence in supporting successful bilingual classroom practices